CD83 is locally regulated and differentially expressed in disturbed murine pregnancy. Issue 4 (October 2019) - Einenkel, Rebekka; Packhäuser, Katrin Regina Helene; Ehrhardt, Jens; Tüngler, Anne; Zygmunt, Marek; Muzzio, Damián Oscar
Abstract : Alterations in the immunologic balance during pregnancy have been associated with poor pregnancy outcomes. The underlying mechanisms are complex and mouse models delivered valuable information on inflammatory imbalance in disturbed pregnancies and served as model to test potential anti-inflammatory therapies. CD83 is a transmembrane protein (mCD83) with a soluble form (sCD83) which possesses strong anti-inflammatory properties. During murine pregnancy, upregulated mCD83 expression induces sCD83 release after in vitro stimulation with LPS, phorbol myristate acetate (PMA) and ionomycin. The release mechanism of sCD83 and its control are yet to be elucidated. In this study, the expression of mCD83 and sCD83 has been extensively studied in the CBA/J × DBA/2J mouse model of pro-inflammatory-mediated pregnancy disturbances. mCD83 was higher expressed on splenic B cells, uterus-draining lymph nodes T cells and dendritic cells from mice with poor pregnancy outcome (PPOM) compared to mice with good pregnancy outcome (GPOM). PPOM, however, was accompanied by lower sCD83 serum levels. In vitro treatment of splenic B cells with progesterone led to a reduction of TIMP1 expression, mCD83 expression and sCD83 release, while TIMP1 treatment had a positive effect on sCD83 availability. These results suggest that tissue and matrix components are involved in the regulation of CD83 in murine pro-inflammatory pregnancies.